Essaying the essay: Nursing scholarship and the hegemony of the laboratory - Lyn Gardner (Nurse Education Today, 2011)
It might appear odd or even perverse to be arguing for the essay as a vehicle for academic thought and writing, particularly given the current emphasis on scientific research and evidence-based practice. In fact, the scholarly essay has virtually ceased to exist as an academic form in practice disciplines such as nursing, excluded by what we will identify and refer to as the hegemony of the laboratory. In a practical as well as an intellectual attempt to reinstate it, this paper is structured in the form of two consecutive short essays. In the first, we identify the character, features and purpose of the scholarly essay and examine its demise as an academic form. In the second, we explore some possible reasons why the essay never became fully accepted as an academic form in nursing. We suggest that the essay is thematically eclectic and stylistically promiscuous, drawing from a broad range of cultural, disciplinary and academic reference points. As such, it presents a challenge to the dominant technical rational approach to academic nursing in both its form and its content, particularly in its disregard for the rigidly imposed genres and structures increasingly demanded by academic nursing journals.